Term structure of commodity futures : How well the recently reintroduced rubber futures on MCX is performing ? - Mohammed Anees, Y.C; Ravi Kumar, J (Rubber Science, 35(1): 97-102., 2022)
Producers expecting their products to be sold at reasonable price are often threatened by the risk of price volatility. The unexpected fall in price of products may affect their profitability. Futures market offers them opportunity to hedge any such unanticipated losses. However, a perfect hedge requires taking of careful and informed positions. Such hedging options for the rubber producers and traders are unstable, particularly in Indian context, as there is possibility of introduction, withdrawal and banning of trading of rubber futures on exchanges at any time. Recently MCX has reintroduced their rubber futures and this study attempts to find the term structure of the future market price movements and the correlation between spot price and futures price during contango and backwardation. The study revealed that, most of the time, the market is in contango and the correlation between the spot price and futures price was the highest during contango.
Keywords: Backwardation; Contango; Futures price; Spot price; Price correlation